Corner point detection for the map of kariah Kg. Bukit Kapar / Siti Sarah Raseli, Afina Amirhussain and Norpah Mahat - Raseli, Siti Sarah; Amirhussain, Afina; Mahat, Norpah (UiTM Press, 2020)
Corner point detection are the important technique for many image processing applications including image enhancement, object detection and pattern recognition. The purpose of this study is to detect the corner points of a map of Kariah Kampung Bukit Kapar image by using Harris Corner Detector. Corner points in an image represents a lot of important information of the image. Detection of corner points accurately is significant to image processing, which can reduce much of the calculations. In this study, the initial technique is smoothing the image and extract the boundary of the image. Then, Harris Corner Detector is used to detect the corner points by considering the amount of corner point detection and run time processing. This study proposed the Harris Corner Detector which can detect 154 points with 12.9552 second.